6=3(v-5)-6v

Simple and best practice solution for 6=3(v-5)-6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=3(v-5)-6v equation:



6=3(v-5)-6v
We move all terms to the left:
6-(3(v-5)-6v)=0
We calculate terms in parentheses: -(3(v-5)-6v), so:
3(v-5)-6v
We add all the numbers together, and all the variables
-6v+3(v-5)
We multiply parentheses
-6v+3v-15
We add all the numbers together, and all the variables
-3v-15
Back to the equation:
-(-3v-15)
We get rid of parentheses
3v+15+6=0
We add all the numbers together, and all the variables
3v+21=0
We move all terms containing v to the left, all other terms to the right
3v=-21
v=-21/3
v=-7

See similar equations:

| 6(1+3k)=-18-67k | | 1.4x+.5=-3.42 | | (-19x)-5=-20x-4 | | 0.6x+4.8=72. | | 8d-7d+3=18 | | 14-2x-11=2x-7 | | (y+6)=6 | | 6x+3=106 | | -40-7x+10x=17 | | 10h+11=h+9h+11 | | 1/4x+14=26 | | x+14+108+42=180 | | g+3/2=3 | | -6n+1+4=-4n-3 | | -6a+3+7a=12-22 | | 15=3(2x-5) | | 7-x/5=-2 | | -5n-2=35 | | b/8b+5=29 | | h+3(3h+4)=-8 | | -4f+11=8-4f+1 | | 3=d3 | | -7-3x=15 | | (4x-3)/5=(2x+11)/3 | | 3x-130=2x | | 50000=x+(x*0.0625) | | 7u-4=-11 | | 23=-4r | | 8x+99+8x+99=9x+170 | | 78+64+7x+3=180 | | 7(-x/5)=-2 | | 4(3x+8)=10x+2x+32 |

Equations solver categories